Accidentally catty eaudiobook - Cassidy, Dakota (Accidentally Paranormal, 2014)
Katie Woods never thought that she'd be forty-one, divorced, and thrust back into the dating world. To start fresh, Katie uproots her veterinary practice to upstate New York—not exactly the hottest dating scene on the planet. But when an unconscious cougar appears at her clinic, Katie's newly single life gets a much needed jolt of the supernatural kind. After Katie examines the cougar and leaves him caged overnight, she's shocked to find a big strapping specimen of young, hot man in its place. And when the scratch she got during the exam results in some unnatural side effects, Katie has more to deal with than her animal attraction to a much younger guy—she has to figure how to stop herself from becoming a cougar of the four-legged variety.